Investigation of the effects and evidence of late Quaternary glaciers on the Binaloud Heights - Abolghasem Amir Ahmadi; Leila Goli Mokhtari; Naemi Tebar Mahnaz (تحقیقات کاربردی علوم جغرافیایی)
The purpose of this study was to identify evidence of late Quaternary glaciers in the northern highlands of Binalood. Topographic maps, satellite imagery and climatic data are the tools and data used in this study. Arc gis 10.4 software was used for data analysis. Quaternary glacier evidences were identified based on four types of evidences including morphic indices, climatic evidences, geomorphological evidences and laboratory indices. Using morphic indexes, the curve lines were identified on topographic maps of satellite imagery, ice-dominated areas, and the effects of 28 glacial circuses. Climatic evidence shows that not only was Quaternary at about 7 degrees cooler than the present time, but its precipitation was almost twice as high as at present. On the other hand, glacier circles, moraines, thales and glacial mounds were the most prominent geomorphologic evidence of glaciers in the Binaloud Heights. Finally, granulometric laboratory indices supplementing the evidence of glaciers have confirmed the existence of glacial sediments at the Binaloud Heights. Also, using Wright's method, the permanent snow boundary line during the reign of Binalood Heights Glaciers was estimated at 2600 m.